Analisa Pengaruh Kualitas Pelayanan, Harga, Dan Promosi Terhadap Kepuasan Pelanggan Pada Perusahaan Pt. Garuda Indonesia - Lucia Lanny (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This research includes descriptive research type of research that aims to explain the relationship between the variables studied. This research is categorized as cross sectional which will be done starting from May 2018 to get the data needed in writing this thesis, researcher conduct research to Garuda customer which located in Indonesia. Primary data is data collected by the researchers themselves from the object of research. Primary data in question through questionnaires given / distributed to Garuda's customers as respondents. Secondary data collection is relatively easy, but has advantages and disadvantages. Researcher obtain secondary data from PT company profile. GARUDA, journals, books, internet and other reading materials related to the factors to be studied. In this study, the variables used and classified into independent variables (independent variables) are service quality (x1), price (x2) and promotion (x3) and dependent variable (non-free variable) ie customer satisfaction (y) .2. It was found that the variable of service quality, price and promotion have contribution or ability to explain the variance of the purchase decision variable by 48,3% while for the rest equal to 51,7% explained by other variable not examined here.